2011
DOI: 10.3109/0142159x.2011.586745
|View full text |Cite
|
Sign up to set email alerts
|

The clinical skills experience of rural immersion medical students and traditional hospital placement students: A student perspective

Abstract: Background: Recent decades have seen an international trend for the development of undergraduate medical programmes in rural locations. These have been considered educationally equivalent alternatives to traditional hospital-based programmes. A pilot Rural Medical Immersion Programme (RMIP) was launched at the University of Otago. Aims: To examine the clinical skills experience of RMIP students and to compare it to that of fifth-year students based in the traditional, often urban and hospital-based, rotations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…These findings are consistent with prior studies that have shown comparable assessment performance for cohorts of rural students 18 and confirms the immense value of longitudinal integrated rural clinical placements in teaching students core clinical skills. 19 The comparability of clinical skills assessment is also consistent with previous studies. 20 Research into the efficacy of rural longitudinal integrated clerkships in South Australia and Canada has demonstrated the educational value in continuity of care, longitudinal exposure and participation in care.…”
Section: Discussionsupporting
confidence: 77%
“…These findings are consistent with prior studies that have shown comparable assessment performance for cohorts of rural students 18 and confirms the immense value of longitudinal integrated rural clinical placements in teaching students core clinical skills. 19 The comparability of clinical skills assessment is also consistent with previous studies. 20 Research into the efficacy of rural longitudinal integrated clerkships in South Australia and Canada has demonstrated the educational value in continuity of care, longitudinal exposure and participation in care.…”
Section: Discussionsupporting
confidence: 77%
“…1 ). In total, five non-randomized controlled trials, 22 , 25 , 34 , 35 , 38 four uncontrolled before-and-after studies, 26 , 30 , 33 , 37 eight post-intervention survey or interview studies, 23 , 24 , 27 29 , 31 , 32 , 39 and one case series study 36 were included.
Figure 1 PRISMA flow diagram showing the number of records and studies identified during the search process, screened for relevance, assessed for eligibility and included in the synthesis.
…”
Section: Resultsmentioning
confidence: 99%
“…Geographically, 12 studies were performed in the USA, 22 – 24 , 26 – 28 , 30 32 , 36 38 three in the European Union, 25 , 34 , 39 and one each in Canada, 29 New Zealand, 35 and Singapore. 33 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initiatives like the Rural Heroes Project 2015 launched by the World Organization of Family Doctors [5] reveal a rather individualistic and narrow-minded approach to solve the increasing need for rural practitioners. In addition, promoters of rural practice use to stress the fact that graduates trained in rural settings tend to rate themselves as better prepared for rural family practice than urbantrained physicians [6,7]. Likewise, rural practitioners organisations and their representatives repeatedly claim for primary health care (PHC) and family practice as the far most important but continuously underrated medical disciplines.…”
mentioning
confidence: 99%